PERAN MUSYRIF DALAM MENUMBUHKAN KESADARAN DIRI BERIBADAH PADA SISWA SEKOLAH AL QUR'AN WAHDAH ISLAMIYAH CIBINONG KABUPATEN BOGOR - Muhammad Hamka; Endin Mujahidin (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2023)
The role of musyrif (dormitory mentors) is crucial in fostering worship awareness among students at Al-Qur'an Wahdah Islamiyah School in Cibinong, Bogor. This study is motivated by the need for deep spiritual guidance for the younger generation to instill worship values in their daily lives. The primary objective of this research is to explore the contributions of musyrif in cultivating students' worship awareness. This study employs a qualitative approach, utilizing observation, interviews, and document analysis for data collection. The findings indicate that musyrif serve as inspiring educators, role models in worship practices, and motivators for students. Additionally, the conducive environment created by musyrif significantly enhances students' understanding and practice of worship. The study concludes that the role of musyrif has a substantial impact on increasing students' worship awareness, encouraging them to perform worship with sincerity and a sense of responsibility